The association between physicians’ exercise counseling and physical activity in patients with cancer: which roles do patients’ satisfaction and previous physical activity levels play? - Depenbusch, Johanna; Haussmann, Alexander; Tsiouris, Angeliki; Schmidt, Laura; Wiskemann, Joachim; Ungar, Nadine; Sieverding, Monika; Steindorf, Karen (Psycho-oncology, 2020)
Objectives The purpose of this study was to examine the association between physicians’ exercise counseling and post-diagnosis physical activity (PA) in patients with cancer by investigating the mediating role of patients’ satisfaction with exercise counseling as well as the moderating role of patients’ previous PA. Methods The study sample consisted of 1002 people with cancer (503 breast, 265 prostate, and 234 colorectal cancer). Participants reported their pre- and post-diagnosis moderate-to-vigorous PA (MVPA) levels, indicated whether their physician had covered different steps of exercise counseling as defined by the 5A framework (Assess, Advise, Agree, Assist, and Arrange) and rated their satisfaction with exercise counseling. A conditional process analysis was used to determine the direct and indirect effects of counseling on post-diagnosis MVPA through satisfaction at different levels of pre-diagnosis MVPA. Results Physicians’ exercise counseling was associated with post-diagnosis MVPA in patients with cancer. However, the association differed by patients’ pre-diagnosis MVPA (P = .039). While counseling was directly associated with higher post-diagnosis MVPA for individuals with low pre-diagnosis MVPA (CI: 0.02-0.20, P = .014), the effect was mediated through satisfaction with exercise counseling for previously highly active individuals (Boot CI: 0.01-0.08). Conclusions Our findings emphasize the relevance of physicians’ exercise counseling for PA in patients with cancer. However, the results indicate that in order to effectively influence patients’ PA, it appears important to provide a comprehensive counseling that is adjusted to the patients’ exercise experiences.